Bioquímica quântica das estatinas, aspirina e anti-hipertensivos - Costa, Roner Ferreira da (2011)
Cardiovascular diseases (CVDs) comprise a large spectrum of heart and blood vessels (arteries and veins) diseases, among which include coronary artery disease, heart attack, angina, acute coronary syndrome, aortic aneurysm, cardiac arrhythmias, heart failure and rheumatic heart disease. Among the major drugs used to treat CVDs are: (i) Statins, which act by inhibiting 3-hidroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase in the process of convention of HMG-CoA to mevalonate, one of the steps of the cholesterol biosynthesis. Observed in clinical trials that the action of statins may reduce levels of bad cholesterol (LDL) between 20% and 60%, reducing the coronary events in 1/3 the period of five years; (ii) The aspirin, with which more than 400 preparations in the U. S. and produces about 20.000 tons annually. After more than a century of clinical practice, aspirin remains the antithrombotic, antipyretic, analgesic and anti-proliferative drug most widely recommended. Its acts by blocking the hormones inflammatory prostanoids biosyntheses by inhibiting ciclooxygenase enzymes COX-1 and COX-2; (iii) the antihypertensives, for which the Converting Enzyme (ACE) is the main target (ACE inhibitors are in market for over 20 years) in order to combat the high blood pressure, which cause changes in blood vessels and heart muscle and lead to heart left ventricular hypertrophy, stroke, myocardial infarction, death sudden, kidney and heart failure, etc. Arterial Hypertension, known popularly as high blood pressure, is a disease more prevalence in the modern world. ACE acts in the regulation of pressure blood via conversion of the decapeptide angiotensin I in a potent vasopressor angiotensin II and also by the inactivation of bradykinin, being a central component of the Renin-Angiotensin-Aldosterone (RAAS), which controls blood pressure and has a strong influence on functions related to the heart and kidneys, as well as contraction of blood vessels. In This work is carried out a quantum biochemical study of statins (atorvastina, rosuvastatin, cerivastatin, mevastatina, simvastatin and fluvastatin), aspirin / bromoaspirin and antihypertensive (captopril, enalapril, lisinopril, ramipril, trandolapril and perindopril) taking advantage of the crystallographic data of binding pocket on proteins such as HMGR, COX-1 (the aspirin was simulated starting from the bromoaspirin data) and ACE, respectively. Computer simulations were performed considering the Density Functional Theory (DFT) in the local density approximation (LDA) exchange functional and PWC correlation with interaction energy between residues of limited to the protein binding pocket of radius r and drugs calculated by the method of molecular fractionation conjugate caps (MFCC). The results for statins suggest that: i) the more (less) effective are atorvastatin and rosuvastatin (simvastatin and fluvastatin), which is consistent with clinical data and values concentrations inhibitory IC 50; (ii) binding pocket at consider a radius 12 ˚A (beyond the range of 9.5 ˚A suggested by strict analysis of crystallographic data) should be considered important to residues as E665, D767, and R702 be considered so that the efficiencies of statins are properly explained. For aspirin / bromoaspirin was used a second order quantum refinement of crystallographic data to demonstrate that the interaction energy with both COX-1 is very nearly the same, which explains results experimental IC 50 similar. The existence of residues attractive and repulsive is highlighted, showing that Arg120 is residue that attracts more salicylic acid after acetylation of Ser530, followed by Ala527, Leu531, Leu359 and Ser353, on the other hand, Glu524 is the residue most effective repellent (intensity comparable to Arg120), having never before been considered important in the residue of site binding of aspirin / bromoaspirin in COX-1. Finally, in the case of antihypertensive drugs, you get what is necessary to consider radius of the binding pocket 16 ˚A to obtain the lisinopropil and ramipril (trandolapril and perindopril) present the higher (lower) interactions energies, which explains the higher (lower) inhibition constant of the same among the anti-hypertensive studied for ACE Drosophila melanogaster.